TPH1 and 5-HT7 Receptor Overexpression Leading to Gemcitabine-Resistance Requires Non-Canonical Permissive Action of EZH2 in Pancreatic Ductal Adenocarcinoma - Prakash Chaudhary (MDPI AG, 2021)
In the present study, we investigated the regulatory mechanisms underlying overexpression of EZH2, tryptophan hydroxylase 1 (TPH1), and 5-HT7, in relation to gemcitabine resistance and CSC survival in PDAC cells. In aggressive PANC-1 and MIA PaCa-2 cells, knock-down (KD) of EZH2, TPH1, or HTR7 induced a decrease in CSCs and recovery from gemcitabine resistance, while preconditioning of less aggressive Capan-1 cells with 5-HT induced gemcitabine resistance with increased expression of EZH2, TPH1, and 5-HT7. Such effects of the gene KD and 5-HT treatment were mediated through PI3K/Akt and JAK2/STAT3 signaling pathways. EZH2 KD or GSK-126 (an EZH2 inhibitor) inhibited activities of these signaling pathways which altered nuclear level of NF-kB, Sp1, and p-STAT3, accompanied by downregulation of TPH1 and 5-HT7. Co-immunoprecipation with EZH2 and pan-methyl lysine antibodies revealed that auto-methylated EZH2 served as a scaffold for binding with methylated NF-kB and Sp1 as well as unmethylated p-STAT3. Furthermore, the inhibitor of EZH2, TPH1, or 5-HT7 effectively regressed pancreatic tumor growth in a xenografted mouse tumor model. Overall, the results revealed that long-term exposure to 5-HT upregulated EZH2, and the noncanonical action of EZH2 allowed the expression of TPH1-5-HT7 axis leading to gemcitabine resistance and CSC population in PDAC.